Building Global Indigenous Media Networks: Envisioning Sustainable and Regenerative Futures around Indigenous Peoples’ Meaningful Representation - Reynaldo A. Morales (Humanities, 2021)
Asserting the right to meaningful representation, challenging the epistemological and methodological expansion of global corporate capitalism and its impacts on Indigenous Peoples’ territories and cultures, aligns with the implementation of global treaties and conventions that are part of key international laws regarding issues of climate change, biodiversity conservation, education, global health, human rights, and sustainable development. Indigenous Peoples have been consistently excluded from nation state visions of modernity and development, which continues to limit their full participation in global sustainable development initiatives and their meaningful representation therein. Increasing the visibility of this struggle is imperative for Indigenous Peoples, particularly around the strategic areas in which the implementation of global sustainable development treaties, policies, and goals continues to affect their rights. This article inquires whether Indigenous Peoples’ emancipatory appropriation of media means from a transnational perspective that breaks their regional enclosure can contribute to decolonize the world. More specifically, it questions how a new Indigenous global media network would contribute to decolonize the relations between Indigenous Peoples and nation states. A wider mapping of Indigeneity that decolonizes sustainable development becomes critical in order to formally document the efforts of Indigenous Peoples to reconstruct and restore their epistemic and material relations. This article questions how an Indigenous global media network around new nexus research can benefit Indigenous Peoples, and make visible the incorporation of the recommendations and principles from international law emanated from the self-determined voices of Indigenous leaders, experts, and policy makers to decolonize global sustainable development goals.